Emergency care of a patient with anaphylactic shock caused by infusion of famotidine after aortic stent graft implantation (1例主动脉覆膜支架植入术后输注法莫替丁致过敏性休克的急救护理) - LI Pengping (李鹏萍); SUN Yulian (孙玉莲); WANG Hongdan (王虹丹) (中西医结合护理)
This paper summarized the nursing management of a patient with anaphylactic shock caused by infusion of famotidine after aortic stent graft implantation. Key interventions of emergency care includes: activating the emergency plan for hypotension, identifying the cause of hypotension, activating the emergency plan for anaphylactic shock, illness condition observation and nursing, and psychological care, etc. After a series of rescue treatment and nursing, the patient's consciousness gradually recovered and vital signs were within normal range. (本文总结1例主动脉覆膜支架植入术后输注法莫替丁致过敏性休克的急救护理经验。急救护理措施包括: 启动低血压应急预案、识别低血压原因、启动过敏性休克应急预案、加强病情观察、开展心理护理等。经过医护一体有序地抢救和护理, 患者意识恢复, 顺利脱机, 生命体征趋于平稳。)